2013
DOI: 10.1002/etc.2080
|View full text |Cite
|
Sign up to set email alerts
|

Mitigating with macrophytes: Submersed plants reduce the toxicity of pesticide‐contaminated water to zooplankton

Abstract: Abstract-In ecotoxicology, appreciation is growing for the influence that ecological interactions have on the toxicity of contaminants, such as insecticides, to sensitive species. Most previous studies, however, have focused on factors that exacerbate insecticide effects on species, while factors that may mitigate these effects have been relatively ignored. In aquatic habitats, a small number of studies have shown that submersed macrophytes can remove some insecticides from the water column via sorption. Altho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 39 publications
(40 reference statements)
2
6
0
Order By: Relevance
“…Whereas the present study demonstrates strong mitigating effects of submersed macrophytes on zooplankton exposed to insecticides, other studies comparing insecticide toxicity to zooplankton in the presence and absence of macrophytes have found mixed evidence of mitigation. For example, the results from the present study are highly consistent with previous work demonstrating that different densities of E. canadensis can strongly mitigate the effects of malathion on D. magna in a biomass‐dependent manner . Brock et al also found some evidence of insecticide mitigation by macrophytes when they contrasted the effects of 35 µg/L of another organophosphate insecticide, chlorpyrifos, between macrophyte ‐ dominated and phytoplankton‐dominated communities using indoor 850 L experimental units.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Whereas the present study demonstrates strong mitigating effects of submersed macrophytes on zooplankton exposed to insecticides, other studies comparing insecticide toxicity to zooplankton in the presence and absence of macrophytes have found mixed evidence of mitigation. For example, the results from the present study are highly consistent with previous work demonstrating that different densities of E. canadensis can strongly mitigate the effects of malathion on D. magna in a biomass‐dependent manner . Brock et al also found some evidence of insecticide mitigation by macrophytes when they contrasted the effects of 35 µg/L of another organophosphate insecticide, chlorpyrifos, between macrophyte ‐ dominated and phytoplankton‐dominated communities using indoor 850 L experimental units.…”
Section: Discussionsupporting
confidence: 92%
“…The degree to which macrophytes actually influence the toxic effects of insecticides in aquatic communities is poorly understood. Recently, Brogan and Relyea examined the mitigating influence of submersed macrophytes on malathion's toxicity to the aquatic zooplankter, Daphnia magna . The authors discovered that malathion was up to 9 times less toxic in the presence of realistic densities of the common macrophyte Elodea canadensis than in the absence of macrophytes (median lethal concentration in absence of macrophytes [LC50 no‐macrophytes ] = 2.8 µg/L).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Attempts have been made of their disposal using different methods: physical -through infiltration (Krutz et al, 2003;Peña et al, 2011), coagulation (Brillas et al, 2003;Hladik et al, 2005), biological -for phytoremediation (Chuluun et al, 2009), culture macrophytes (Beketov and Liess, 2008;Matby et al, 2009;Brogan and Relyea, 2013), and the use of biotechnological methods (Hladik et al, 2005;Kanissery and Sims, 2011;Nawaz et al, 2011). For many years, the studies on the use of adsorbents for the removal of various herbicides from water have been conducted.…”
Section: Introductionmentioning
confidence: 97%
“…Prorocentrum minimum (dinoflagellate) was reported to be the most affected by the herbicide and most suitable as model organism for ecotoxicity assessments. Mitigation effects of insecticide Malathion caused by macrophyte Elodea canadensis on Daphnia magna were studied by Brogan and Relyea (2013) for potential ecological interactions on environmental contaminants. It was found that increasing densities of Elodea decreased the toxicity of Malathion on Daphnia.…”
mentioning
confidence: 99%